2007
DOI: 10.1111/j.1532-5415.2007.01202.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Trial to Improve Prescribing Safety in Ambulatory Elderly Patients

Abstract: This study demonstrated the effectiveness of a computerized pharmacy alert system plus collaboration between healthcare professionals in decreasing potentially inappropriate medication dispensings in elderly patients. Coupling data available from information systems with the knowledge and skills of physicians and pharmacists can improve prescribing safety in patients aged 65 and older.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
113
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(113 citation statements)
references
References 30 publications
0
113
0
Order By: Relevance
“…40 These CPs support other initiatives to reduce the use of highrisk medications by the elderly and improve the management of osteoporosis in women who have suffered a fracture. One initiative successfully interchanged patients aged ≥ 65 years who were receiving diazepam, a long-acting benzodiazepine that should be avoided in elderly patients, to safer alternative treatments.…”
Section: Continuing Carementioning
confidence: 99%
“…40 These CPs support other initiatives to reduce the use of highrisk medications by the elderly and improve the management of osteoporosis in women who have suffered a fracture. One initiative successfully interchanged patients aged ≥ 65 years who were receiving diazepam, a long-acting benzodiazepine that should be avoided in elderly patients, to safer alternative treatments.…”
Section: Continuing Carementioning
confidence: 99%
“…60 A prescriber education intervention was associated with a reduction in PIPE from 5.3% to 4.3% of prescriptions over 2 years, 58 while a computerized pharmacist alert resulted in inappropriate medications dispensed to fewer intervention patients (1.8%) compared with usual care patients (2.2%). 59 Medication review interventions have also been associated with reductions in inappropriate prescribing, including the report by Hanlon et al (1996) in a group of older adults with polypharmacy, in which inappropriate prescribing was reduced by 24% compared with 6% in a control group. 56 Monane et al (1998) found that a computerized drug utilization review alert system combined with telephone calls to a subset of physicians was associated with change to a more appropriate medication in 24% of the cases, but the rate of change ranged from 40% for long half-life benzodiazepines to 2%-7% of drugs that may have been contraindicated based on patients' self-reported drug history.…”
Section: Why Prescribing May Not Be Ceasedmentioning
confidence: 99%
“…54 Potentially inappropriate prescribing in the elderly (PIPE) is an area of medication prescribing research that has grown, in part as a response to the problems caused by polypharmacy in the elderly. 55,56 It has been studied at the health systems level, 57 among patients in Medicare managed care, 55,58 and in ambulatory 59 and community-dwelling patients. 60 A prescriber education intervention was associated with a reduction in PIPE from 5.3% to 4.3% of prescriptions over 2 years, 58 while a computerized pharmacist alert resulted in inappropriate medications dispensed to fewer intervention patients (1.8%) compared with usual care patients (2.2%).…”
Section: Why Prescribing May Not Be Ceasedmentioning
confidence: 99%
“…35 A current (October 2010) PubMed search on the terms "CPOE" and "computerized prescription order entry" with "safety" limited to RCTs produces only 3 studies, all conducted in the same large health maintenance organization (HMO) in 2006 and 2007. [36][37][38] When all HMO members aged 65 years or older were randomized to a CPOE-based alerting system that triggered when any of 11 potentially inappropriate medications for the elderly were prescribed (n = 29,840) or to a "usual care" control group (n = 29,840), Raebel et al found that the rate of potentially inappropriate dispensings per 100 patients during the 1-year follow-up was 1.85, compared with 2.20 in the control group (difference of 0.0035 dispensings per patient, P = 0.002). 36 However, in a similarly designed study targeted to pregnant women, the intervention was successful in reducing the use of pregnancy-risk medications but had to be discontinued because of false-positive alerts attributable to computer system limitations.…”
mentioning
confidence: 99%
“…[36][37][38] When all HMO members aged 65 years or older were randomized to a CPOE-based alerting system that triggered when any of 11 potentially inappropriate medications for the elderly were prescribed (n = 29,840) or to a "usual care" control group (n = 29,840), Raebel et al found that the rate of potentially inappropriate dispensings per 100 patients during the 1-year follow-up was 1.85, compared with 2.20 in the control group (difference of 0.0035 dispensings per patient, P = 0.002). 36 However, in a similarly designed study targeted to pregnant women, the intervention was successful in reducing the use of pregnancy-risk medications but had to be discontinued because of false-positive alerts attributable to computer system limitations. 37 Additionally, an RCT of CPOE-delivered reminders found no significant effect on provider adherence to recommended laboratory testing guidelines at initiation of pharmacotherapy.…”
mentioning
confidence: 99%